2018
DOI: 10.26434/chemrxiv.5743638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bulk Contributions Modulate the Sum-Frequency Generation Spectra of Interfacial Water on Model Sea-Spray Aerosols

Abstract: Vibrational sum-frequency generation (vSFG) spectroscopy is used to determine the molecular structure of water at the interface of palmitic acid monolayers. Both measured and calculated spectra display speci c features due to third-order contributions to the vSFG response which are associated with nite interfacial electric potentials. We demonstrate that theoretical modeling enables to separate the third-order contributions, thus allowing for a systematic analysis of the strictly surface-sensitive, second-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The two bands roughly centered at 3250 and 3550 cm -1 wavenumbers are attributed to the relatively stronger and weaker hydrogen bonded water molecules, respectively. 33 At a relatively low [Nd]t of 400 nM, the OH region is significantly affected with a near uniform drop in the bimodal intensities. From the XFNTR results (Figure 2) this corresponds to ~ 1/3 coverage of Nd 3+ species.…”
Section: Toc Graphicmentioning
confidence: 99%
See 1 more Smart Citation
“…The two bands roughly centered at 3250 and 3550 cm -1 wavenumbers are attributed to the relatively stronger and weaker hydrogen bonded water molecules, respectively. 33 At a relatively low [Nd]t of 400 nM, the OH region is significantly affected with a near uniform drop in the bimodal intensities. From the XFNTR results (Figure 2) this corresponds to ~ 1/3 coverage of Nd 3+ species.…”
Section: Toc Graphicmentioning
confidence: 99%
“…18,20 SFG spectroscopy provides an indirect measure of ion adsorption, through the changes happening to the interfacial water structure or the surface functional groups. [26][27]33 Recently, Sthoer et al reported an observation of overcharging of Y 3+ and La 3+ ions at arachidic acid (AA) monolayers with SFG spectroscopy. 27 The intensity of -OH region signal (3200 -3700 cm -1 ) decreased as the bulk concentration is increased from 100 nM to 10 M, which is typical due to the decreasing surface charge and disturbed interfacial water organization.…”
Section: Toc Graphicmentioning
confidence: 99%
“…The SFG signal mainly consists of two broad bands centered at ~3200 cm -1 and ~3400 cm -1 , which are assigned to stronger hydrogen bonded and weaker hydrogen bonded water populations at the interface, respectively. 56 The https://doi.org/10.26434/chemrxiv-2023-dj4m0-v3 ORCID: https://orcid.org/0000-0003-3278-5570 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 quantitative definition of hydrogen bonding strength is an active topic of discussion.…”
Section: Vibrational Sum Frequency Spectroscopymentioning
confidence: 99%